(untitled) (Economics and region, 2024)
This research aims to scrutinise the Layer 2 ecosystem within the Ethereum blockchain, providing a basis for informed decision-making by users with limited technical expertise when selecting Layer 2 projects. The research is based on data collected from the L2BEAT community. The article outlines the key technical concepts underlying various Layer 2 projects on the Ethereum blockchain, and describes the characteristics of projects such as ZK Rollup, Validium, Optimistic Rollup and Optimium. It juxtaposes the project types identified by the L2BEAT team with a simplified framework of the Ethereum Layer 2 ecosystem proposed by Vitalik Buterin. Ethereum blockchain Layer 2 scaling projects are audited, focusing on the indicators "total value locked in escrow agreements" and "share of value locked in total project value". The technologies used to verify the authenticity of the system state in Ethereum Blockchain Layer 2 scaling projects are explained. An analysis of fraud detection approaches in Layer 2 blockchain scaling projects is undertaken. Techniques for validating messages transmitted over Layer 2 blockchain bridges are described. An assessment of the security of the Layer 2 blockchain ecosystem is presented, along with an evaluation of the popularity of such projects among users. The study concludes that for users, pricing in the Ethereum Layer 2 blockchain ecosystem is key, with Arbitrum One emerging as the undisputed leader in scaling projects. In terms of bridges, user preference leans towards those that facilitate the withdrawal of funds in the event of dishonest or malicious behaviour by the bridge operator.